WELDING INSTALLATION WITH REDUCED IMPACT ON THE NETWORK - Tirshu M.S.; Zaitev D.A.; Uzun M.N. (Problems of the Regional Energetics)
This paper offers a new technical solution to implement arc welding installation. Existing electric arc welders have a significant impact on consumers that are connected near the connection point of it. This effect is greater the longer the feeder. If the installation is connected to the end of the feeder, the impact on neighboring consumers is so large that can be damaged appliances. The proposed technical solution is based on the idea of using the battery as a buffer. The battery is designed so that its capacity was sufficient to meet the instantaneous current peaks that occur during operation. Along with this, in the proposed technical solution, an innovative element is a current pulse source. The novelty lies in the special algorithm of this current source. The proposed algorithm allows the power consumption of the network in a controlled manner and without abrupt jumps.